ANALISIS PERAN PENGGUNAAN MULTIMEDIA PADA PROSES PEMBELAJARAN PAI DI SEKOLAH MENENGAH PERTAMA - Aninda Sitta Rozakiatul Ula; Aida Arini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the role of multimedia in the teaching process of Islamic Religious Education (PAI) at the junior secondary school level. A qualitative descriptive approach was employed using a case study method. Data were collected through observation, interviews, and documentation. The findings reveal that multimedia serves as an interactive learning tool that enhances students’ cognitive understanding and supports the development of spiritual character. The types of multimedia used include animated videos, digital presentations, and online platforms such as YouTube and Google Meet. These tools encourage active learning, increase student engagement, and contribute positively to both comprehension of religious material and the formation of spiritual attitudes. In conclusion, multimedia not only improves knowledge acquisition but also fosters essential spiritual values in Islamic education.